Buenas Prácticas Docentes desde la subjetividad estudiantil - Mogrovejo Gualpa, Javier Oscar (2024)
The precision of what can be considered as a good practice could be set from a moralistic perspective, not a pedagogical or psychological one, an aspect that influences higher education. Some courses do not contribute to personal and professional development of students; therefore it is essential to know the perception of university students on good teaching practices, in order to discover the impact that these learning experiences have had on their professionalization. At the same time, to reflect on the factors that intervene in the student's subjectivity to estimate that a teaching practice is good. The participants were former students of Psychology at the University of Guayaquil. The method applied was phenomenological with purposive sampling. The information was obtained through observation, checklist and in-depth interview; the results indicated that in the perception of the participants, the cognitive elements are prioritized to denote the teaching practice as good,leaving aside the affective and personality traits. It was concluded that good teaching practice demand to be holistic and integral, encompassing thinking, feeling, ethical, personological and social dimensions, elements not perceptively considered by university students. A good teaching practice is challenging because it implies breaking with the rigidity of institutional regulations. It is necessary to make teaching practice more flexible in order to achieve a free and critical education.